Longitudinal Evidence for High-Level Patellar Tendon Strain as a Risk Factor for Tendinopathy in Adolescent Athletes - Falk Mersmann; Theresa Domroes; Meng-Shiuan Tsai; Nikolaos Pentidis; Arno Schroll; Sebastian Bohm; Adamantios Arampatzis (SpringerOpen, 2023)
Abstract Background High tendon strain leads to sub-rupture fatigue damage and net-catabolic signaling upon repetitive loading. While high levels of tendon strain occur in adolescent athletes at risk for tendinopathy, a direct association has not yet been established. Therefore, in this prospective longitudinal study, we examined the hypothesis that adolescent athletes who develop patellar tendon pain have shown increased levels of strain in advance. Methods In 44 adolescent athletes (12-17 years old), patellar tendon mechanical properties were measured using ultrasonography and inverse dynamics at four time points during a season. Fourteen athletes developed clinically relevant tendon pain (SYM; i.e., reduction of the VISA-P score of at least 13 points), while 23 remained asymptomatic (ASYM; VISA-P score of > 87 points). Seven cases did not fall into one of these categories and were excluded. Tendon mechanical properties of SYM in the session before the development of symptoms were compared to a randomly selected session in ASYM. Results Tendon strain was significantly higher in SYM compared to ASYM (p = 0.03). The risk ratio for developing symptoms was 2.3-fold higher in athletes with tendon strain ≥9% (p = 0.026). While there was no clear evidence for systematic differences of the force applied to the tendon or tendon stiffness between SYM and ASYM (p > 0.05), subgroup analysis indicated that tendon force increased prior to the development of symptoms only in SYM (p = 0.034). Discussio The study provides novel longitudinal evidence that high tendon strain could be an important risk factor for patellar tendinopathy in adolescent athletes. We suggest that inadequate adaptation of tendon stiffness to increases in muscle strength may occur if adolescent athletes are subject to mechanical loading which does not  provide effective tendon stimulation.